Skin lesions on the face – dermatoscopy as a diagnostic tool to facilitate diagnosis and selection of appropriate therapeutic management (Journal of Face Aesthetics, 2021)
This paper presents clinical and dermatoscopic features of selected skin lesions, which are relatively common in the facial region according to the authors and available literature. By using dermatoscopy it is possible to show the differences between the analysed skin lesions, which may be clinically very similar, sometimes indistinguishable. It is worth emphasising that finding in dermatoscopy any structures suggesting a malignant lesion should be equal to a decision about surgical excision. In doubtful situations the examined lesion should be considered as potentially malignant and also classical surgical excision with histological evaluation should be recommended. However, in case of lesions affecting a large area of the skin, an advanced biopsy from the most suspicious area is acceptable. The use of other treatment methods such as laser or cryotherapy is justified only when the diagnosis of benign lesion is unambiguous.
Keywords: dermatoscopy; facial lesions; diagnostic methods